Influence of substitutions and roles on kinematic variables in professional soccer players - Laterza, F.; Savoia, C.; Bovenzi, A.; D`Onofrio, R.; Pompa, D.; Annino, G.; Manzi, V. (International Journal of Sports Medicine, 2024)
In soccer, roles and substitutions can make it unclear how different physical capacities decrease over time and impact performance. This investigation aimed to analyze kinematic parameters and their changes over game time, and provide information to effectively prescribe training programs. Data from four professional teams were analyzed, and all the teams competed in the Italian First Division (Serie A). Average metabolic power and high-intensity activities associated with critical moments in the match were considered in the comparisons. The video analysis system STATS SportVU collected the data during official matches. Players were assigned to a specific group according to their time played, categorized as follows: 0-15`, 15-30`, 30-45`, 45-60`, 60-75`, 75-90`, and > 90 min. Different roles, including forwards and wingers (FW), midfielders (MF), center-backs (CB), and side-backs (SB) were also considered. Significant differences (p<0.05) were found in different roles and within roles at different times played. The results highlighted how MF performance decreased over time, whereas CB was unaffected by time. SB spent more time at very high velocity than other roles, independently from the time played. These findings provide valuable information about the physical demands of official soccer matches and could be used to review training prescriptions.